Perancangan Trainer Elektronika Digital Sebagai Media Pembelajaran Teknik Listrik Politeknik Unisma - Syarifatul Izza; Gillang Al Azhar (JTEV (Jurnal Teknik Elektro dan Vokasional), 2022)
One of the main subjects in the Electrical Engineering Department at Polytechnic of Unisma Malang is the basics of digital electronics course. The main problems that have been encounters in studying digital electronics course are the lack of trainer modules that support the learning process. The main learning material always encounters some problems, which is becoming the main goal for this research to reduce the problems in the digital electronics learning process, by creating a trainer module to support the course. The Research and Development (R&D) method is used as the main method for the data retrieval, which greatly affects the stages for creating the trainer module. There are 4 stages: (1) Defining, (2) Design, (3) Development, and (4) Realization, that produce the trainer module that consists of 3 logic gate modules (OR-gate, AND-gate, NOT-gate), which supported by 4 other modules. They are the Power Supply module, Input block module, and 2 Output Modules (LED module and 7-Segment Module). The test was carried out by involving 5 lectures and 8 students, which include the feasibility, observation, and the impact aspect. The result is magnificent, it shows 86.4% for the feasibility aspect, 93.75% for the observation aspect, and it raises the quality of the study outcome from 75% to 94% which show how good the impact of the trainer module for support the learning process for the digital electronics course.